BEM-ESTAR NO CONTEXTO DA FRONTEIRA BRASIL/BOLÍVIA: UMA ANÁLISE A LUZ DA FELICIDADE INTERNA BRUTA - Marcus Vinícius Barbosa Vieira (2024)
This work is a study on well-being in the border context. Based on the literature on the economics of happiness, data from Brazil and Bolivia were analyzed with the aim of understanding well-being based on the parameters highlighted in the theory of Gross National Happiness (GNH) – an indicator used in Bhutan, a country in South Asia. Recently, this indicator was used as a parameter to evaluate happiness in the cities of Lavras/MG and Curitiba/PR. In this sense, with the aim of presenting solutions to increase well-being in the border region according to the FIB and considering the guidelines of the City Sports and Leisure Program (PELC), activities in the field of leisure were explored that could provide the increase in well-being on the Brazil/Bolivia border, more specifically, on the Corumbá (BRA) and Puerto Quijarro/Puerto Suarez (BOL) border. The specific objective of this research is to present the Gross Domestic Happiness (GNH) indicator, highlighting the use of leisure as a tool for increasing border well-being. The specific objectives of the work are to evaluate the components of GNH and propose solutions capable of increasing the level of border well-being through public leisure policies. From the empirical study, it was possible to catalog public goods linked to the theme of leisure in the border area in question and which can increase the level of well-being of the local population. Furthermore, it was possible to establish mechanisms related to well-being in the southern region of Mato Grosso and the opportunities for implementing sport and recreation as a tool for local development, mainly in the health and education pillars. As a proposal for action, the research product consists of a dynamic script to be delivered to the postgraduate program in border studies (PPGEF). This itinerary includes the qualification of points, the distance from the limit between Brazil and Bolivia to each public asset of interest to the user, and georeferencing with geographic coordinates of leisure equipment available in Corumbá/MS, already accessible to the border population. The solution aims to help mainly Bolivians, who are sometimes unaware of local opportunities capable of improving well-being at the border.